An Ethnography Study of Stress Management among Sundanese, Chinese, and Javanese - Fadhilah, Savira Maghfiratul; Heikal, Jerry; Savitri, Fania Mutiara; Mangkuto, Shidiq Umar; Saputra, Tubagus Chandra (Journal of Advanced Multidisciplinary Research, 2024)
This ethnographic study examines how the cultural backgrounds influence stress management among Sundanese, Chinese, and Javanese officers in the Directorate General of X. Through a qualitative ethnographic approach, data were gathered via in-depth interviews, observations, and document analysis to uncover the unique stress management methods employed by each cultural group. The findings demonstrate that Sundanese officers focus on work-life balance and rely on supportive social networks, guided by the values of "Silih Asah, Silih Asih, Silih Asuh," which emphasize care, support, and self-improvement. Chinese officers prioritize discipline, hard work, and harmony, using structured task management and involving senior colleagues in decision-making, influenced by Confucian, Taoist, and Buddhist beliefs. Javanese officers rely on spirituality and empathy, following "Tepa Selira" principles, which promote understanding and respect in relationships, and include prayer and parental guidance in stress coping strategies. Despite these distinct methods, all three cultural groups emphasize the importance of support systems, in the workplace. This study suggests that understanding these cultural approaches can help organizations design culturally sensitive support systems to enhance employee well-being and performance. Future research could expand these findings by including more participants and diverse work settings to better understand culturally influenced stress management across Indonesia.